Analysis on dynamic performance of different track transition forms using the discrete element/finite difference hybrid method. (1st April 2020) - Shi, Can; Zhao, Chunfa; Zhang, Xu; Andersson, Andreas
Highlights: Establish track transition models by combining DEM with FDM. Compared dynamic performances of different types of track transitions. Effect of the transition section parameters on dynamic performance of track transitions. The two-part transition section has better dynamic performance. The inverted trapezoid transition section has better performance than the trapezoid transition section. Abstract: To analyze the mesodynamic and macrodynamic performance of the track transitions more precisely, a bridge-embankment transition model has been established by combining the discrete element method (DEM) with the finite difference method (FDM). In this model, the DEM is utilized to model sleepers and ballast particles with complex shape, and the FDM is applied to simulate the abutment, transition section and embankment. The DEM/FDM coupled model is then achieved by exchanging displacements, velocities, and contact forces at the interface. Afterwards, the influence of the transition section parameters and transition forms on dynamic behaviour of the track-substructure system is studied under measured rail seat load. The numerical simulations indicate that the increase of the transition section elastic modulus, decrease of the backfill slope values and the transition form of trapezoid backfill following by inverted trapezoid backfill can provide a better displacement gradient between the abutment and the embankment. Additionally, the results show that the inverted trapezoid transition form can provide a better transition of the track dynamic performance than the trapezoid transition form and the embankment soil over the wedge-shape backfill has the tendency to propagate along the slope toward the embankment section under the moving train load for the trapezoid transition form.